2009
DOI: 10.2144/000113125
|View full text |Cite
|
Sign up to set email alerts
|

Mouse embryo cryopreservation utilizing a novel high-capacity vitrification spatula

Abstract: Embryo cryopreservation is an indispensable technique in reproductive programs and in animal facilities where genetically modified mice are used extensively. Here we report the use of a vitrification spatula (VS) that can be readily homemade and has a large holding capacity to vitrify preimplantation mammalian embryos in a micro-drop employing ultra-rapid cooling in liquid nitrogen (LN2). Vitrified one-cell embryos and morulae have high survival rates after thawing, and the fertility of the derived progeny is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The surface techniques ( Fig. 1) include EM grid (Steponkus et al 1990, Martino et al 1996, minimum drop size (MDS; Arav 1992, Arav & Zeron 1997, Cryotop (Hamawaki et al 1999, Kuwayama & Kato 2000, Cryoloop (Lane et al 1999a(Lane et al , 1999b, Hemi-straw (Vanderzwalmen et al 2000), solid surface (Dinnyes et al 2000), nylon mesh (Matsumoto et al 2001), Cryoleaf (Chian et al 2005), direct cover vitrification (Chen et al 2006), fiber plug (Muthukumar et al 2008), vitrification spatula (Tsang & Chow 2009), Cryo-E (Petyim et al 2009), plastic blade (Sugiyama et al 2010), and Vitri-Inga (Almodin et al 2010). To the tubing techniques (Fig.…”
Section: Germplasm Cryopreservationmentioning
confidence: 99%
“…The surface techniques ( Fig. 1) include EM grid (Steponkus et al 1990, Martino et al 1996, minimum drop size (MDS; Arav 1992, Arav & Zeron 1997, Cryotop (Hamawaki et al 1999, Kuwayama & Kato 2000, Cryoloop (Lane et al 1999a(Lane et al , 1999b, Hemi-straw (Vanderzwalmen et al 2000), solid surface (Dinnyes et al 2000), nylon mesh (Matsumoto et al 2001), Cryoleaf (Chian et al 2005), direct cover vitrification (Chen et al 2006), fiber plug (Muthukumar et al 2008), vitrification spatula (Tsang & Chow 2009), Cryo-E (Petyim et al 2009), plastic blade (Sugiyama et al 2010), and Vitri-Inga (Almodin et al 2010). To the tubing techniques (Fig.…”
Section: Germplasm Cryopreservationmentioning
confidence: 99%
“…We have conducted a series of experiments with ovine embryos to improve survival rate after cryopreservation by using vitrification with minimum volume methods (Cryotop and Spatula MVD). These two vitrification methods have been previously reported for human (Kuwayama, 2007) and mice embryos (Tsang and Chow, 2009), respectively. In a recent study, we found that ovine IVP embryos vitrified with Cryotop and Spatula MVD showed acceptable in vitro survival and development rate (dos Santos Neto et al, 2015).…”
Section: Are We Ready To Skip the Fresh Embryo Transfer?mentioning
confidence: 99%
“…The vitrification spatula (VS; Tsang and Chow, 2009) and plastic blade (Sugiyama et al, 2010) are similar to the cryoloop (Lane et al, 1999) in their overall topology. All of them have their sample docking domain attached to the ceiling of the cap of cryotube to facilitate tight and easy sealing.…”
Section: Tip-type Carriersmentioning
confidence: 99%